(untitled) (Olhares, 2019)
Positive argumentation about the importance of the art like emancipation skill and fundamental object at the educational process. Speaks about development of sensibility and its important rule for subjectivity`s enhancement, and its range of action on the social life. Starting at the educational prospects by Ana Mae Barbosa, Jacques Rancière and Paulo Freire, and the Karl Marx’s ontological conception, develop a debate about the value of the art on the knowledge acquirement process and individual emancipation, deepening arguments about emancipatory power of artistic activity on pedagogic process.